Basic English learning assistance for students of Pondok Pesantren Rahmatullah Lempake - Amelia, Mahda; Paramitha, Devy Indah (Universitas Muhammadiyah Magelang, 2025)
In the era of globalization, English proficiency is a crucial skill for enhancing individual competitiveness. Adolescence is an ideal stage for language acquisition due to more mature cognitive abilities. This community service program was designed to address the lack of English language learning at the Pondok Pesantren Rahmatullah Lempake in Samarinda, a problem primarily caused by limited teaching staff. The main goal of this activity was to equip students with foundational English knowledge, empowering them to become more competitive and competent individuals in society. The program, conducted over 12 meetings, provided basic English instruction to 9th-grade Wustho students. The methodology included a preparation stage, followed by implementation using the service-learning method, and concluded with a comprehensive evaluation. The evaluation results demonstrated a notable improvement in both understanding and motivation among the participants. Specifically, the students' basic English language skills showed an increase of 60-80%, highlighting the program's effectiveness in bridging the educational gap and fostering a positive learning environment.